2019
DOI: 10.1002/jcp.28190
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA‐211 promotes invasion and migration of colorectal cancer cells by targeting FABP4 via PPARγ

Abstract: Fatty acid binding protein 4 (FABP4) is a novel tumor regulator that is abnormally expressed in many human cancers. In our study, upregulated microRNA‐211 (miR‐211) and reduced FABP4 expression were detected in colorectal cancer (CRC) patients and CRC cells. Mimic miR‐211 or anti‐miR‐211 were transfected to investigate the effects of miR‐211 on SW480 cells. The results showed that miR‐211 promoted but anti‐miR‐211 inhibited cell migration, invasion, and epithelial–mesenchymal transition (EMT) of SW480 cells. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In accordance with the results of our study, FABP4 was identified as a tumor suppressor in multiple cancers. In colorectal cancer, FABP4 was found to be downregulated and its upregulation inhibited the migration, invasion, and proliferation of cancer cells (37). In lung cancer, it was determined that the expression of FABP4 can be induced by the transcriptional activity of PPAR γ, mediating lipolysis and tumor growth suppression (38).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the results of our study, FABP4 was identified as a tumor suppressor in multiple cancers. In colorectal cancer, FABP4 was found to be downregulated and its upregulation inhibited the migration, invasion, and proliferation of cancer cells (37). In lung cancer, it was determined that the expression of FABP4 can be induced by the transcriptional activity of PPAR γ, mediating lipolysis and tumor growth suppression (38).…”
Section: Discussionmentioning
confidence: 99%
“…So far, fewer clinical studies concerning the association between FABP4 and FABP6 and CRC are reported [13, 19, 20]. This article aims to explore the relationship between FABP4 and FABP6 and the pathogenesis of CRC and its potential as a serum biomarker with potential value in the diagnosis and prognosis of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide a new perspective to interrogate the prognostic role of differentially expressed immunity genes in CRC through identification of their receptors. Among the 10 immune genes of prognostic value, used to build our model, Fatty Acid Binding Protein 4 (FABP4) [36,37], NGF [38,39], Resistin Like Beta (RETNLB) [40,41], Urocortin (UCN) [42,43], Vasoactive Intestinal Peptide (VIP) [44,45], Nerve Growth Factor Receptor (NGFR) [46,47] have been implicated in direct or indirect involvement in regulation of CRC development and metastasis through other pathways. However, IGKV1-33, IGKV2D-40, IGLV6-57, and OXTR have not been previously associated with CRC.…”
Section: Agingmentioning
confidence: 99%